Produção científica da área da Química no desenvolvimento da oceanografia no Brasil Scientific productivity of the Chemistry sector to the development of oceanography in Brasil - Luiz Drude de Lacerda; Rozane Valente Marins (Química Nova, 2010)
This paper analyses the scientific contribution of chemists and of the Brazilian Chemical Society (SBQ) and its publications to the development of Oceanography in Brazil, as well as major drivers of this participation. A total of 528 articles were analyzed. Most articles (72%) originated in research groups not associated with graduate programs in oceanography. Nearly 50% dealt with the contamination of the marine environment, followed by chemical process studies (32%) and analytical methods development (15%). SBQ journals contributed with 78 articles (14.7% of the total), and rank 1st (QN) and 2nd (JBCS) among scientific journals publishing the analyzed articles.